Penguasaan 4 (Empat) Prasyarat Dasar Aritmatika untuk Meningkatkan Kemampuan Siswa Sekolah Dasar dalam Menyelesaikan Soal Matematika - Susdarwono, Endro Tri (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2020)
The purpose of this study discusses how mastery of 4 (four) basic prerequisites of arithmetic which includes the ability to count, make Arithmetic / multiples, complement especially Nines and ten, and the concept of place values in numbers affect students' ability to solve math problems consisting of addition, subtraction, multiplication, and multiplication. The approach in this study uses a descriptive approach, the method used is a combination of qualitative and quantitative methods. A qualitative approach is used to describe the basic arithmetic mastery of students including numeracy, making Arithmetic / multiples numbers, complements especially nines and ten, and the concept of place values in numbers. The quantitative approach uses statistical tests with canonical correlation analysis to answer the relationship and influence between understanding of basic arithmetic mastery on the ability to solve math problems related to addition, subtraction, multiplication and division. From the results of the canonical weight and canonical loading function 1, it can be concluded that there is indeed a significant relationship between the dependent variate and the independent variate or basic arithmetic mastery and the students' ability to do math problems is indeed correlated together.